Digesta markers for evaluating the effect of exogenous enzymes on nutrient digestibility in beef feedlot cattle - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2017)
Dissertation (MSc Agric)--University of Pretoria, 2017.